Paleomagnetic analysis of deformation and rotation associated with the HuÌsaviÌk-Flatey Fault, northern Iceland - Chapman, William Alan Longhurst (Carleton Digital Commons, 2016)
The HuÌsaviÌk-Flatey Fault is a 110°-striking oceanic transform fault exposed on land in northern Iceland. South of the HuÌsaviÌk-Flatey Fault, there is a distinct curvature in the strikes of lavas and dikes on the peninsula of Flateyjarskagi: lavas far from the fault strike NW-SE, but change in clockwise fashion to NE-SW strikes close to the fault. Dike strikes change similarly, transitioning from NNE-SSW to E-W. I use paleomagnetic methods to determine whether the curving orientation of these structures is original or whether it reflects tectonic rotation. I present new paleomagnetic data from 8 sites (49 lava flows) on the peninsulas of Flateyjarskagi, TjoÌˆrnes, and TroÌˆllaskagi. From these data it is clear that rocks have rotated, and rotation increases with proximity to the HuÌsaviÌk-Flatey Fault, some of the rocks may have rotated more than 170° (Â±17°) since the fault's initiation 8.5-8.0 Ma. This rotation may have been accommodated by a number of mechanisms, including simple shear, small block rotation, or tectonically driven processes related to a dying spreading ridge in western Iceland. The dying ridge (known as the SkagafjoÌˆrÃ°ur Paleo- Rift) and the Northern Volcanic Zone to the west were simultaneously active from 8.5 Ma to 3.0 Ma, possibly contributing to additional rotation on both vertical and non- vertical axes. These results are important for understanding not only the development of the HuÌsaviÌk-Flatey Fault in northern Iceland, but also deformation associated with oceanic transform faults in general.